Interculturalità e Humanitätsgedanke: dalla prospettiva tardo-illuminista di Herder agli sguardi sull’Africa nel romanzo postcoloniale tedesco “Usambara” di Christof Hamann (2007) (Altre Modernità, 2019)
As this contribution shows, the increasing production of German-language postcolonial novels over the last fifteen years has contributed to enhance the dialogue with the vast debate on cultural anthropology promoted by the European late Enlightenment, especially on issues of ethnicity and the ethical relationship to “otherness” as Humanität. Herder has proved a crucial interpreter of it. Explorations in East Africa have featured prominently in Christoph Hamann’s work. Before and after his novel Usambara (2007), he has shared with others the study of mountain symbolism as referred to the ascent of Kilimanjaro, focussing on the relationship between historical event, colonial propaganda and mythography. Going beyond the interest in exoticism and orientalism on the basis of Said’s reflections, German Studies have evolved towards a new appraisal of the intermediality which is inherently bound to the experiential interweaving of exploration, discovery and conquest in the former German colonies